Resonant Multiple Light Scattering for Enhanced Photon Harvesting in Dye‐Sensitized Solar Cells. (28th May 2014) - Kim, Jihun; Lee, Horim; Kim, Dong Young; Seo, Yongsok
<x xml:space="preserve">Abstract</x> A new benchmark for DSSC performances is set using a novel dye and fabricating a very efficient resonant light‐scattering device with a high photocurrent and good stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>